Komunikasi Partisipatif Resimen Mahasiswa Koordinator Wilayah 1 Surabaya dalam Meningkatkan Minat Mahasiswa Terhadap Bela Negara - Hamdani; Iswadi (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the participatory communication implemented by the Student Regiment (Menwa) Coordinator of Region 1 Surabaya in its efforts to increase university students' interest in national defense. Stemming from the issue of declining student interest in Menwa activities, the research explores how communication plays a vital role in fostering awareness and participation. Using the theory of participatory communication influenced by Paulo Freire’s ideas and a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings show that the communication carried out by Menwa is active and inclusive, directly engaging students and successfully raising awareness of the importance of national defense. This study contributes to the field of communication science, particularly in the implementation of communication strategies in civic education contexts. The research recommends a more humanistic and dialogic communication approach to attract younger generations to national issues.